The Philippine revolution in the Bicol region, (Narrative of the Philippine Revolution in the Provinceof Albay). - Ataviado, Elías M (National Historical Commission c2011, 2011)
Vol 2 : February 1899 to April 1900.
Includes bibliographical references and index
Php 814.00
DD Knowledge
Keywords: Albay (Philippines) -- History